Propuesta de un manual de funciones, valuación de puestos y un reglamento de admisión y empleo para la empresa "Distribuifamiliar S.C." de la ciudad de Quito - Satama Jumbo, Johanna Maritza (2014)
The present research seeks as general objective, the "Proposal of a Manual of Functions, Accounts Management and Regulation of Admission and employment for the DISTRIBUIDOR FAMILIAR S.C company of Quito´s City ", so to guide, facilitate, and have a better development of each of its employees in the areas and positions they hold; the success and permanence of a company for so many years in the market has been the responsibility of the General Manager, who has been considered by many as a leader for its employees, projecting improvement and entrepreneurship in each, with joint effort with his talent human. The aims of this research is to avoid continuing with an everyday, boring and moonlighting job performance, making dynamics, clear, accurate and concise activities, the project was developed taking into account the results of the survey conducted for all staff of the company and the interview with General Manager. In the process of all investigated we used different methods that were considered necessary for better development, among which are used: deductive method which was applied for analysis of the company of the principles, purposes, and if proven and valid, shall we apply to solve them, the Inductive Method was applied to perform a direct observation of how the company is at a glance, the Analytical Method which allowed us to analyze the situation of the company, which tools handled internally in other words if they have a mission, vision, business policies, if they have manual of functions, if they have a regulation of admission and employment and if they conduct a valuation of positions to employees, in other words to know how is schematic the company, as the functions assigned to its Talent, work environment between employees and the Employer. With everything stated above, is proposed and is presented as a complement technical procedures such as direct observation, from which we got data collection and information of each employee of the company , past events within the same whether they are real, social and economic; the art of the interview, which was used to collect information through the set of questions, which was made to the Manager of the company DISTRIBUIDORA FMAILIAR S.C., the survey technique, which is a valuable tool to help and of great importance in the times of data collection. From all of the above and based on the results obtained it follows that the DISTRIBUIDORA FAMILIAR S.C. Company of Quito, located by the sector Amaguaña, currently has thirty three employees, including administrative and operational staff, have five managers who are owners and partners of the company. With all the above said, the company lacks an organizational strategy, in other words does not have a mission, they do not have a vision, do not handle values and quality policies, nor have an organization chart, the research carried out, with the investigation conducted, the development of a manual functions is proposed, making the Accounts Management and prepare a Regulation of Admission and Employment, which serves as a support for a better development of all its employees.